The impact of trust, motivation and rewards on knowledge sharing attitudes among the secondary and higher secondary level students’: evidence from Bangladesh - Rahman, Muhammad Sabbir; Bashir, Hussain (Emerald Group Publishing Limited, 2014)
Purpose – This paper’s aim is to inspect the influence of trust, motivation and rewards on knowledge-sharing attitudes among secondary and higher secondary students in Bangladesh. Design/methodology/approach – A sample of 200 Bangladeshi students from secondary and higher secondary-level educational institutions in Dhaka city participated in this study. Data were analysed using exploratory factor analysis followed by confirmatory factor analysis and structural equation modelling techniques. Findings – The findings suggested that trust variables play a significant role in encouraging knowledge-sharing behaviour among the students. Practical Implications – This research also provides a guideline to teachers and policymakers on enhancing a knowledge-sharing environment among secondary and higher secondary-level students. Originality – This paper is a pioneer in understanding knowledge-sharing patterns among secondary and higher secondary students in a developing country such as Bangladesh. Keywords Bangladesh, Secondary students, Higher secondary students, Trusts, Motivation and reward systems, Secondary students. Paper type Research paper